A zero-shrinkage glass fiber veil, its preparation method and application

CN117706713BActive Publication Date: 2026-10-23YUEYANG AOYUAN COMMUNICATION MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311785857.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2026-10-23
Estimated Expiration
2043-12-22

AI Technical Summary

Technical Problem

聚酯涤纶扎纱实际稳定物态177℃/10min≤2.4m/%,接触PE料熔融体的280℃高温时,材料的热收缩率一定会超出物性标准,或多或少会影响PBT套管的圆整,从而造成对光纤的影响

Benefits of technology

[0024]综上所述,本发明提供的零收缩率玻璃纤维扎纱保留了无碱玻璃纤维纱的优点,同时克服了其横向受力容易脆断的缺点,能够替代目前光缆用聚酯涤纶扎纱,解决聚酯涤纶纱热收缩率大,在光缆芯成绞捆扎时容易造成光纤套管勒痕变形、光纤信号传输衰减的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117706713B_ABST
    Figure CN117706713B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of optical cable, and provides a zero-shrinkage glass fiber yarn, a preparation method and application thereof.The present application uses alkali-free glass fiber yarn as raw material, and sets a layer of resin film on the surface of the alkali-free glass fiber yarn.The components of the resin film include acrylic ester copolymer, wear-resistant agent, softening agent and antistatic agent.When the glass fiber yarn is subjected to transverse force, the film can play the role of cushioning, and the glass fiber yarn is not directly stressed, so that the breakage is avoided, and the process requirements of optical cable processing are met.The zero-shrinkage glass fiber yarn provided by the present application retains the advantages of alkali-free glass fiber yarn, and overcomes the shortcoming that the alkali-free glass fiber yarn is easily brittle broken under transverse stress, and can replace the polyester terylene yarn used in the optical cable, and solve the problems that the polyester terylene yarn has large thermal shrinkage, and the optical fiber jacket is easily deformed and the optical fiber signal transmission is attenuated when the optical cable core is stranded and bundled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical cable technology, and in particular to a zero-shrinkage glass fiber binding yarn, its preparation method, and its application. Background Technology

[0002] Optical fiber cables, as the primary carriers of information transmission, are mainly classified into three types: power composite optical cables, stranded optical cables, and central loose tube optical cables. The optical fiber is placed within an engineering plastic PBT sheath. The PBT sheath must maintain a perfectly round shape; any compression or deformation will generate force that affects the optical fiber. When the optical fiber is subjected to lateral pressure, the transmitted signal will attenuate or be interrupted.

[0003] Power composite optical cables and stranded optical cables are made by bundling multiple PBT optical fiber tubes together with yarn, and then sheathing them with engineering plastic PE. Currently, the most commonly used binding yarn is polyester yarn. PE material is originally a granular, rigid material, which needs to be melted into a paste at 280℃ using an extruder and applied to the optical cable core. The actual stable physical state of polyester binding yarn is ≤2.4m / min at 177℃. When in contact with the molten PE material at 280℃, the material's thermal shrinkage rate will inevitably exceed the standard physical properties, more or less affecting the roundness of the PBT tube, thus impacting the optical fiber.

[0004] Therefore, there is an urgent need in this field to develop a binding yarn that is insensitive to high temperatures and does not experience high-temperature heat shrinkage. Summary of the Invention

[0005] In view of this, the present invention provides a zero-shrinkage glass fiber binding yarn, its preparation method, and its application. The zero-shrinkage glass fiber binding yarn provided by the present invention is insensitive to high temperatures, does not undergo high-temperature thermal shrinkage, and its mechanical properties meet the process requirements of optical cable manufacturing.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0007] A zero-shrinkage glass fiber yarn includes alkali-free glass fiber yarn and a resin film attached to the surface of the alkali-free glass fiber yarn.

[0008] The raw materials for preparing the resin film, by weight, include: 100 parts of acrylate copolymer, 3-15 parts of abrasion resistant agent, 2-10 parts of softener, and 1-10 parts of antistatic agent;

[0009] The raw materials for preparing the acrylate copolymer, by weight, include: 5-12 parts acrylic acid, 5-12 parts methacrylic acid, 350-510 parts ethyl acrylate, 50-110 parts styrene, 200-300 parts deionized water, and 10-15 parts sodium hydroxide solution; the raw materials for preparing the acrylate copolymer also include a crosslinking agent, an initiator, and an emulsifier, wherein the mass of the crosslinking agent is 1%-12% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene, the mass of the initiator is 0.1%-10% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene, and the mass of the emulsifier is 1%-5% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene.

[0010] Preferably, the wear-resistant agent is a dimethyl silicone oil-based wear-resistant agent;

[0011] The softener is a hydrophilic silicone softener.

[0012] The antistatic agent is a glass fiber anionic antistatic agent.

[0013] Preferably, the crosslinking agent is AAEM crosslinking agent; the initiator is aqueous persulfate; and the emulsifier is one or more of nonylphenol polyoxyethylene ether and sodium dodecyl sulfate.

[0014] Preferably, the concentration of the sodium hydroxide solution is 5-15 wt%.

[0015] Preferably, the method for preparing the acrylate copolymer includes the following steps:

[0016] Acrylic acid, methacrylic acid, ethyl acrylate, styrene, deionized water, sodium hydroxide solution, crosslinking agent, initiator and emulsifier are mixed and polymerized to obtain an acrylate copolymer; the polymerization reaction temperature is 30-80℃ and the reaction time is 3-5 min.

[0017] The present invention also provides a method for preparing the zero-shrinkage glass fiber yarn described above, comprising the following steps:

[0018] The acrylate copolymer, abrasion resistant agent, softener and antistatic agent are mixed to obtain the preform;

[0019] After impregnating the alkali-free glass fiber yarn in the preform, it is sequentially molded and cured to obtain the zero-shrinkage glass fiber yarn.

[0020] Preferably, the molding process is based on controlling the amount of adhesive applied to each 1 kg of glass fiber yarn to be 10-20 wt%.

[0021] Preferably, the curing temperature is 80–140°C and the curing time is 2–5 min.

[0022] The present invention also provides the application of the zero-shrinkage glass fiber binding yarn described in the above-described scheme or the zero-shrinkage glass fiber binding yarn described in the above-described scheme in optical cable core bundling.

[0023] This invention provides a zero-shrinkage glass fiber yarn, comprising alkali-free glass fiber yarn and a resin film attached to the surface of the alkali-free glass fiber yarn; the resin film, by weight, comprises: 100 parts of acrylate copolymer, 3-15 parts of abrasion-resistant agent, 2-10 parts of softener, and 1-10 parts of antistatic agent; the acrylate copolymer, by weight, comprises: 5-12 parts of acrylic acid, 5-12 parts of methacrylic acid, 350-510 parts of ethyl acrylate, and 50-110 parts of styrene. The raw materials for preparing the acrylate copolymer include 200-300 parts deionized water and 10-15 parts sodium hydroxide solution. The crosslinking agent, initiator, and emulsifier are also included in the preparation process. The mass of the crosslinking agent is 1%-12% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene. The mass of the initiator is 0.1%-10% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene. The mass of the emulsifier is 1%-5% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene. Alkali-free glass fiber yarn (also known as E-type glass fiber yarn) has advantages such as low shrinkage under high temperature, resistance to strong acids, strong alkalis, and oils, and its fiber properties are soft and highly variable. However, alkali-free glass fiber yarn is prone to brittle breakage under transverse mechanical stress, which does not meet the process requirements of optical cable manufacturing. This invention uses acrylate copolymer, abrasion resistant agent, softener, and antistatic agent as raw materials for the resin film. A layer of resin film is deposited on the surface of alkali-free glass fiber yarn. The resin film has extensibility, softness, abrasion resistance, mechanical bending properties, and antistatic properties. When the glass fiber yarn is subjected to lateral force, the film layer can act as a cushioning layer, preventing the glass fiber yarn from being directly stressed and thus ensuring that it does not break, thereby meeting the process requirements of optical cable processing. When the zero-shrinkage glass fiber binding yarn of this invention is applied to the stranding and bundling of optical cable cores, the force value is 1.6 times higher than that of polyester binding yarn, the process speed of optical cable core stranding and bundling is increased by 40%, and the material cost is 30% lower than that of polyester binding yarn. Furthermore, process verification shows that the glass fiber binding yarn of this invention is physically stable at a high temperature of 280°C, and the thermal shrinkage rate reaches zero shrinkage over a length of 100 meters, which can ensure the stability of optical cable quality.

[0024] In summary, the zero-shrinkage glass fiber binding yarn provided by this invention retains the advantages of alkali-free glass fiber yarn while overcoming its disadvantage of being easily brittle under lateral stress. It can replace the polyester binding yarn currently used in optical cables, solving the problems of high thermal shrinkage rate of polyester yarn, which easily causes fiber optic sleeve marks and deformation, and fiber optic signal transmission attenuation when the optical cable core is twisted and bundled. Attached Figure Description

[0025] Figure 1 This is a flow chart of the preparation process of the zero-shrinkage glass fiber yarn of the present invention. Detailed Implementation

[0026] This invention provides a zero-shrinkage glass fiber yarn, comprising alkali-free glass fiber yarn and a resin film attached to the surface of the alkali-free glass fiber yarn;

[0027] The raw materials for preparing the resin film, by weight, include: 100 parts of acrylate copolymer, 3-15 parts of abrasion resistant agent, 2-10 parts of softener, and 1-10 parts of antistatic agent;

[0028] The raw materials for preparing the acrylate copolymer, by weight, include: 5-12 parts acrylic acid, 5-12 parts methacrylic acid, 350-510 parts ethyl acrylate, 50-110 parts styrene, 200-300 parts deionized water, and 10-15 parts sodium hydroxide solution; the raw materials for preparing the acrylate copolymer also include a crosslinking agent, an initiator, and an emulsifier, wherein the mass of the crosslinking agent is 1%-12% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene, the mass of the initiator is 0.1%-10% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene, and the mass of the emulsifier is 1%-5% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene.

[0029] Unless otherwise specified, all raw materials used in this invention are commercially available.

[0030] The zero-shrinkage glass fiber yarn provided by this invention includes alkali-free glass fiber yarn. In this invention, the preferred type of the alkali-free glass fiber yarn is 100tex to 300tex, specifically 100tex, 130tex, 150tex, 200tex, and 300tex.

[0031] The zero-shrinkage glass fiber yarn provided by the present invention includes a resin film attached to the surface of the alkali-free glass fiber yarn. In the present invention, the raw materials for preparing the resin film include: 100 parts of acrylate copolymer, 3-15 parts of abrasion resistant agent, preferably 5-10 parts, 2-10 parts of softener, preferably 3-8 parts, and 1-10 parts of antistatic agent, preferably 2-8 parts.

[0032] In this invention, the wear-resistant agent is preferably a dimethyl silicone oil-based wear-resistant agent. This invention does not specify the particular type of the dimethyl silicone oil-based wear-resistant agent; any agent well-known to those skilled in the art can be used. The softener is preferably a hydrophilic organosilicon softener. This invention does not specify the type of the hydrophilic organosilicon softener; any agent well-known to those skilled in the art can be used. The antistatic agent is preferably a glass fiber anionic antistatic agent. The main components of the glass fiber anionic antistatic agent are anionic surfactants, polymers, conductive agents, and antioxidants, wherein the anionic surfactant is preferably sodium dodecyl sulfonate. This invention does not specify the particular type of the glass fiber anionic antistatic agent; any agent well-known to those skilled in the art can be used.

[0033] In this invention, the abrasion-resistant agent can enhance the bonding between the adhesive film and the glass fiber yarn, making it less prone to damage under friction and ensuring a low yarn breakage rate; the softener can modify the hardness of the bond between the adhesive film and the glass fiber yarn, improve bending deformation, and enhance the fit between the glass fiber binding yarn and the PBT optical fiber sheath; the antistatic agent can eliminate static electricity in the glass fiber binding yarn, ensuring that the high-speed cable laying does not jump or pull the optical cable core to swing during application in optical cable manufacturing equipment, thus ensuring the quality of the optical cable and stable, non-attenuated optical fiber signal transmission.

[0034] In this invention, the raw materials for preparing the acrylate copolymer include: 5-12 parts of acrylic acid, preferably 10 parts; 5-12 parts of methacrylic acid, preferably 10 parts; 350-510 parts of ethyl acrylate, preferably 402 parts; 50-110 parts of styrene, preferably 90 parts; 200-300 parts of deionized water, preferably 260 parts; and 10-15 parts of sodium hydroxide solution. The raw materials for preparing the acrylate copolymer preferably also include a crosslinking agent, an initiator, and an emulsifier. The mass of the crosslinking agent is 1%-12% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene, preferably 3%-10%. The mass of the initiator is 0.1%-10% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene, preferably 3%-6%. The mass of the emulsifier is 1%-5% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene, preferably 2%-3%.

[0035] In this invention, the concentration of the sodium hydroxide solution is preferably 5-15 wt%; the crosslinking agent is preferably AAEM crosslinking agent, the chemical name of which is ethylene glycol diacetoacetate methacrylate, CAS number 21282-97-3; the initiator is preferably an aqueous persulfate; the aqueous persulfate is preferably one or more of ammonium persulfate (APS), potassium persulfate (KPS), and sodium persulfate (NPS); the emulsifier is preferably one or more of nonylphenol polyoxyethylene ether and sodium dodecyl sulfate.

[0036] In this invention, the method for preparing the acrylate copolymer preferably includes the following steps:

[0037] Acrylic acid, methacrylic acid, ethyl acrylate, styrene, deionized water, sodium hydroxide solution, crosslinking agent, initiator and emulsifier are mixed and polymerized to obtain an acrylate copolymer; the polymerization temperature is preferably 30-80°C, more preferably 60°C, and the polymerization time is preferably 3-5 min.

[0038] After the copolymerization reaction is completed, no further processing is required to obtain the acrylate copolymer; the molecular weight of the acrylate copolymer is preferably 20,000 to 50,000.

[0039] In this invention, the zero-shrinkage glass fiber yarn has a shrinkage rate of 0 when heated at 280°C for 10 minutes.

[0040] The present invention also provides a method for preparing the zero-shrinkage glass fiber yarn described above, comprising the following steps:

[0041] The acrylate copolymer, abrasion resistant agent, softener and antistatic agent are mixed to obtain the preform;

[0042] After impregnating the alkali-free glass fiber yarn in the preform, it is sequentially molded and cured to obtain the zero-shrinkage glass fiber yarn.

[0043] Figure 1 This is a flow chart of the preparation process of the zero-shrinkage glass fiber yarn of the present invention. The following is in conjunction with... Figure 1 Please provide a detailed explanation.

[0044] This invention involves mixing an acrylate copolymer, an abrasion resistant agent, a softener, and an antistatic agent to obtain a preform. In this invention, the mixing is preferably carried out in a stainless steel drum of a disperser, the mixing temperature is preferably room temperature, the mixing speed is preferably 1400 r / min, and the dispersion time is preferably 10–15 min.

[0045] After obtaining the preform, the present invention impregnates alkali-free glass fiber yarn in the preform and then sequentially molds and cures it to obtain the zero-shrinkage glass fiber yarn. In the present invention, the impregnation is preferably a trough impregnation; the present invention preferably places the alkali-free glass fiber yarn on a yarn feeding frame, places the preform in the impregnation tank, and pulls the alkali-free glass fiber yarn inward through the impregnation tank for impregnation; the material of the impregnation tank is preferably 304 stainless steel; the molding is preferably carried out in a molding machine, which has a built-in scraper, and the amount of glue applied is controlled by the pressure of the scraper; in a specific embodiment of the present invention, the molding is preferably controlled to control the amount of glue applied per 1 kg of glass fiber yarn to be 10-20 wt%.

[0046] In this invention, the curing temperature is preferably 80–140°C, more preferably 90–120°C, and the curing time is preferably 2–5 minutes. In a specific embodiment of this invention, the yarn after passing through the molding machine is preferably fed into a hot air furnace for heating and baking. During the baking process, the alkali-free glass fiber yarn and the adhesive layer self-adhere and cross-link. After exiting the hot air furnace, the yarn is preferably wound into a roll. This invention, through impregnation, molding, and curing, attaches a resin film to the outer layer of each monofilament of the alkali-free glass fiber yarn, thereby changing the weakness of the glass fiber yarn being easily broken when subjected to mechanical forces in the transverse direction, making it meet the requirements for use in optical cable manufacturing.

[0047] This invention also provides the application of the zero-shrinkage glass fiber binding yarn described in the above-described scheme, or the zero-shrinkage glass fiber binding yarn described in the above-described scheme, in optical cable core bundling. This invention does not specify any particular method for the application; methods well-known to those skilled in the art can be used.

[0048] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0049] The softener used in the following examples is a hydrophilic softener of model TY-168, purchased from Dongguan Taiyang New Material Technology Co., Ltd.; the abrasion-resistant agent used in the following examples is model SR-243, purchased from Guangdong Leibang New Material Co., Ltd.; the antistatic agent used in the following examples is model 6012, purchased from Shenzhen Quanyimei Technology Co., Ltd.

[0050] Example 1

[0051] Preparation of acrylate copolymer: By mass, 10 parts acrylic acid, 10 parts methacrylic acid, 402 parts ethyl acrylate, 90 parts styrene, 260 parts deionized water, and 10 parts sodium hydroxide solution (concentration 15wt%) were mixed. Then, AAEM crosslinking agent, initiator (ammonium persulfate), and emulsifier (sodium dodecyl sulfate) were added. The amount of crosslinking agent added was 3% of the total mass of acrylic acid, methacrylic acid, ethyl acrylate, and styrene; the amount of initiator added was 2% of the total mass of acrylic acid, methacrylic acid, ethyl acrylate, and styrene; and the amount of emulsifier added was 2% of the total mass of acrylic acid, methacrylic acid, ethyl acrylate, and styrene. The mixture was reacted at 60℃ for 5 min to obtain the acrylate copolymer.

[0052] 100 parts of acrylate copolymer, 5 parts of abrasion resistant agent, 5 parts of softener, and 3 parts of antistatic agent are added to a stainless steel tank of a disperser and dispersed for 15 minutes at room temperature and a dispersion speed of 1400 rpm to prepare a preform.

[0053] Take 100tex alkali-free glass fiber yarn, place it on a yarn feeding rack, place the pre-made material in an impregnation tank, pull out the alkali-free glass fiber yarn through the impregnation tank to impregnate it with glue, and then put it into a molding machine for molding. Control the pressure of the built-in scraper in the molding machine to control the glue application amount to 15wt% per 1kg of glass fiber yarn. After the yarn exits the molding machine, it enters a hot air furnace for heating and baking for 2 minutes at a temperature of 100℃. The glass fiber yarn and the glue self-adhere and cross-link. After exiting the hot air furnace, the yarn is wound up and rolled into a roll to obtain zero-shrinkage glass fiber yarn.

[0054] Example 2

[0055] The other conditions are the same as in Example 1, except that the type of alkali-free glass fiber yarn is replaced with 130tex.

[0056] Example 3

[0057] The other conditions are the same as in Example 1, except that the type of alkali-free glass fiber yarn is replaced with 150tex.

[0058] Example 4

[0059] The other conditions are the same as in Example 1, except that the type of alkali-free glass fiber yarn is replaced with 200tex.

[0060] Example 5

[0061] The other conditions are the same as in Example 1, except that the type of alkali-free glass fiber yarn is replaced with 300tex.

[0062] Performance testing:

[0063] The properties of the zero-shrinkage glass fiber yarns prepared in Examples 1-5 were tested, and the properties of polyester yarns were also tested for comparison. The testing standards used are as follows:

[0064] (1) Alkali-free E-type glass fiber roving: GB / T 18369-2022 Glass fiber untwisted roving.

[0065] (2) Tensile strength at break: GB / T 6604-2017 Polyester industrial filament.

[0066] (3) High temperature shrinkage rate: GB / T 6604-2017 Polyester industrial filament.

[0067] (4) Breakage rate: GB / T 18369-2022 Glass fiber untwisted roving.

[0068] (5) Yarn width: GB / T 18369-2022 Glass fiber untwisted roving.

[0069] The test results are shown in Tables 1 and 2.

[0070] Table 1. Test results of zero-shrinkage glass fiber yarn binding performance

[0071]

[0072] Table 2. Performance test results of polyester yarn

[0073]

[0074] As can be seen from the data in Tables 1 and 2, the glass fiber binding yarn prepared by this invention has stronger tensile strength at break compared with conventional polyester yarn, which can meet the process requirements of optical cable bundling. It also exhibits good high-temperature resistance, with a shrinkage rate of 0 after heating at 280℃ for 10 minutes, and a lower rate of yarn breakage and flyaways. Furthermore, the yarn width of this invention is wider than that of conventional polyester yarn products. Width affects the pressure exerted during optical cable core winding; a wider product results in less pressure on the cross-sectional area of ​​the optical fiber sheath, making it less prone to winding pressure marks.

[0075] The transverse breaking force of the alkali-free E-type glass fiber raw material and the zero-shrinkage glass fiber yarn prepared by the examples was tested, and the results are shown in Table 3.

[0076] Table 3 Results of transverse fracture force test

[0077]

[0078]

[0079] As can be seen from Table 3, the present invention coats the surface of alkali-free E-type glass fiber with a resin film, which can significantly improve the transverse breaking force of alkali-free E-type glass fiber, thereby ensuring that it will not break during use and meeting the process requirements of optical cable processing.

[0080] The results of the above embodiments show that the zero-shrinkage glass fiber binding yarn provided by the present invention retains the advantages of alkali-free glass fiber yarn, while overcoming its disadvantage of being easily brittle under lateral stress. It can replace the polyester binding yarn currently used for optical cables, and solve the problems of high thermal shrinkage rate of polyester yarn, easy to cause fiber optic sleeve marks and deformation, and fiber optic signal transmission attenuation when the optical cable core is twisted and bundled.

[0081] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A zero-shrinkage glass fiber yarn, characterized in that, Includes alkali-free glass fiber yarn and a resin film attached to the surface of the alkali-free glass fiber yarn; The raw materials for preparing the resin film, by weight, include: 100 parts of acrylate copolymer, 3-15 parts of abrasion resistant agent, 2-10 parts of softener, and 1-10 parts of antistatic agent; The raw materials for preparing the acrylate copolymer, by weight, include: 5-12 parts acrylic acid, 5-12 parts methacrylic acid, 350-510 parts ethyl acrylate, 50-110 parts styrene, 200-300 parts deionized water, and 10-15 parts sodium hydroxide solution; the raw materials for preparing the acrylate copolymer also include a crosslinking agent, an initiator, and an emulsifier, wherein the mass of the crosslinking agent is 1%-12% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene, the mass of the initiator is 0.1%-10% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene, and the mass of the emulsifier is 1%-5% of the total mass of the acrylic acid, methacrylic acid, ethyl acrylate, and styrene.

2. The zero-shrinkage glass fiber yarn according to claim 1, characterized in that, The wear-resistant agent is a dimethyl silicone oil-based wear-resistant agent; the softener is a hydrophilic organosilicon softener.

3. The zero-shrinkage glass fiber yarn according to claim 2, characterized in that, The antistatic agent is a glass fiber anionic antistatic agent.

4. The zero-shrinkage glass fiber yarn according to claim 1, characterized in that, The crosslinking agent is AAEM crosslinking agent; the initiator is aqueous persulfate; and the emulsifier is one or more of nonylphenol polyoxyethylene ether and sodium dodecyl sulfate.

5. The zero-shrinkage glass fiber yarn according to claim 1, characterized in that, The concentration of the sodium hydroxide solution is 5-15 wt%.

6. The zero-shrinkage glass fiber yarn according to claim 1, characterized in that, The preparation method of the acrylate copolymer includes the following steps: Acrylic acid, methacrylic acid, ethyl acrylate, styrene, deionized water, sodium hydroxide solution, crosslinking agent, initiator and emulsifier are mixed and polymerized to obtain an acrylate copolymer; the polymerization reaction temperature is 30~80℃ and the reaction time is 3~5min.

7. The method for preparing zero-shrinkage glass fiber yarn according to any one of claims 1 to 6, characterized in that, Includes the following steps: The acrylate copolymer, abrasion resistant agent, softener and antistatic agent are mixed to obtain the preform; After impregnating the alkali-free glass fiber yarn in the preform, it is sequentially molded and cured to obtain the zero-shrinkage glass fiber yarn.

8. The preparation method according to claim 7, characterized in that, The molding process is based on controlling the amount of adhesive applied to each 1 kg of glass fiber yarn to be 10-20 wt%.

9. The preparation method according to claim 7, characterized in that, The curing temperature is 80~140℃ and the time is 2~5 minutes.

10. The application of the zero-shrinkage glass fiber binding yarn according to any one of claims 1 to 6 or the zero-shrinkage glass fiber binding yarn prepared by the preparation method according to any one of claims 7 to 9 in the binding of optical cable cores.

Citation Information

Patent Citations

  • Glass fiber yarn for blocking water for optical cable

    CN103061136A

  • Styrene copolymer emulsion for dip coating of glass fibers and preparation method and application of styrene copolymer emulsion

    CN103087244A